Analysis Of Productive Behavior of Underprivileged Families in Sindetanyar Village, Besuk District, Probolinggo Regency - Ahmad Noviyanto; Hari Wahyono; Lisa Rokhmani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research is motivated by the productive behavior of underprivileged families in utilizing social assistance from the Hope Family Program or PKH. This study uses a qualitative approach to the type of phenomenology. The location of this research is in Sindetayar Village, Besuk District, Probolinggo Regency. The selection of these informants used a snowball sampling approach with 10 informants. Data collection techniques were carried out by interview, observation, and documentation. Based on the results of the study, it can be concluded that the work owned by underprivileged families is only sufficient for basic needs and the PKH assistance provided by the government does not change the behavior patterns of underprivileged families who are more likely to use the social assistance to cover debts or buy consumptive goods